(untitled) (Journal of actual problems of jurisprudence, 2016)
This article discusses the issues associated with the concept of property in foreign countries. In the study conducted an analysis of criminal law of Spain, France, Holland, Germany, Switzerland, Poland, Sweden. Also the author of the comprehensive study, especially on international legislation in the field of criminal-law protection of the property. Based on the consideration of foreign law on the criminal- law protection of intellectual property a detailed comparative-legal analysis of international and criminal legislation of the Republic of Kazakhstan in order to benefit from positive foreign experience in the criminal law of the Republic of Kazakhstan.